Research on the aging-suitability of community outdoor spaces in Zhengzhou based on the analytic hierarchy process and semantic differential method - Gao, Chang; Wang, Shengnan; Li, Pengpeng; Jia, Wenbo; Feng, Kai (Frontiers in Public Health, 2024)
Background: As global populations age, the suitability of community outdoor spaces for elderly residents has become a critical urban planning concern. However, comprehensive evaluation methods for assessing these spaces are lacking. Objective: This study aims to evaluate the aging-suitability of community outdoor spaces in Zhengzhou, China, and provide optimization suggestions for urban planners and policymakers. Methods: An evaluation index system was established using the Analytic Hierarchy Process (AHP), with aging-suitability as the goal layer. The criteria layer included outdoor behavioral activities, green space configuration, transportation and road systems, and basic service facilities. The Semantic Differential (SD) method was employed to conduct a comprehensive evaluation among elderly residents in three communities (A, B, and C) in Zhengzhou city. Results:The evaluation revealed that elderly residents generally had a favorable assessment of their community spaces' aging-suitability. Community A received the highest overall rating. Green space configuration and transportation systems emerged as critical factors influencing aging-suitability.Conclusions: The combined AHP-SD approach proved effective in evaluating the aging-suitability of community outdoor spaces. The study identified key areas for improvement in each community, with variations in strengths and weaknesses across the three sites. Implications: Based on the findings, optimization suggestions are proposed in four aspects: enhancing outdoor behavioral activities, improving green space landscapes, refining road transportation systems, and upgrading basic service facilities. These recommendations can guide urban planners and policymakers in creating more age-friendly community environments.